Evaluasi Beban Kerja Spa Terapis Di Legian Kuta-Bali - Irwanti, Ni Ketut Dewi (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2019)
Spa therapists play an important role in the spa services industry. The resulting performance has an impact on customer satisfaction and the existence of the spa business itself. So that spa therapists are required to be able to show optimal performance. Efforts to meet optimal service can be a source of fatigue that can reduce the performance of spa therapists. At Y Spa, a therapist takes ± 45 minutes — 1 hour to serve 1 customer. Whereas when the level of customer visits is high, a therapist must serve 8-10 customers in one day, so it is not uncommon for them to have to work more than 8 working hours in general. Massage and foot care activities performed by the therapist are very at risk of increasing musculoskeletal complaints. The goal of this study is to evaluate the workload of Spa therapist. For this reason, an observational study was conducted on 14 spa therapists. To evaluate the workload, measurements of working pulse, room microclimate, subjective complaints, and skeletal muscle complaints were measured. The microclimates measured are light intensity, noise, dry temperature, wet temperature, and environmental humidity. From the results of the study found that the therapist spa workload is quite heavy. For this reason, ergonomic interventions should be sought through improving working conditions.